Does Child Temperament Modify the Overweight Risk Associated with Parent Feeding Behaviors and Child Eating Behaviors?: An Exploratory Study - Tate, Allan D. (Appetite, 2016)
BACKGROUND: Child temperament is a measure of an individual's behavioral tendencies. The primary objective of this study was to examine whether child temperament modified the overweight risk associated with parent feeding behaviors and child eating behaviors. METHODS: A sample of predominantly African American, Midwest families (N=120) recruited from four metropolitan primary care clinics participated in this cross-sectional, mixed methods study. Parents reported on feeding practices, child eating behaviors, and child temperament. RESULTS: Difficult temperament was not statistically related to parent feeding practices or child eating behaviors (p>0.05). Tests of interaction indicated that the risk of child overweight differed by difficult temperament and easy temperament for two child eating behaviors (emotional eating and food fussiness, p<0.05). For example, the effect of food fussiness decreased the risk of overweight for difficult temperament children but increased overweight risk for easy temperament children. Further, the effect of emotional eating increased the risk of overweight for difficult temperament children but decreased overweight risk for easy temperament children. CONCLUSIONS: Tailoring parent-level interventions to child temperament or promoting environments that trigger less reactive individual responses may be effective in lowering risk of child overweight.